Efeitos do glifosato sobre o desenvolvimento embrionário, larval e adulto do peixe-zebra (Danio rerio) - Ames, Jaíne (2021)
Glyphosate-Based Herbicides (GBH) are the most used pesticides in the world and pose risks to environmental health and to non-target organisms. This work aimed to verify the toxicity, the mechanisms involved and the consequences of exposure to GBH in zebrafish (Danio rerio). For this, we developed two independent chapters, one experimental and the other a systematic review with meta-analysis. In the first, we analyzed the toxicity of an GBH in concentrations allowed by legislation in drinking water throughout the embryonic and larval development of zebrafish. Zebrafish embryos were exposed to the permitted concentrations of glyphosate in drinking water in zebrafish embryos, half (250 μg/L), maximum (500μg/L) it's the double (1000 μg/L) of permitted concentrations in drinking water of glyphosate Roundup Original DI®. Mortality, hatch rate, heart rate, malformations, behavior and biochemical markers were evaluated. Our results point to an increase in mortality within 6 hours after fertilization (hpf) at a concentration of 500 μg/L, an increase in hatching rate and heart rate at 48 hpf at all concentrations. An increase in the number of animals with malformations was recorded in all concentrations tested. Regarding biochemical markers, we found a decrease in the activity of AChE and GST enzymes. In the second, we study the mechanisms involved in glyphosate toxicity in the embryonic, larval and adult stages of zebrafish through a meta-analytic procedure. For this, a search was performed in the PubMed and Science Direct databases. Articles evaluating the effect of glyphosate on zebrafish published up to July 2020 were considered. After obtaining the data, the R software was used to perform the meta-analytical tests. Selection by title, abstract and full text was performed, and 20 original research articles with zebrafish exposed to commercial and/or pure glyphosate were obtained. The systematic review and meta-analysis study showed that glyphosate induces increased mortality, causes malformations, affects hatching and heart rate in the embryonic and larval stages. At high concentrations, we found a higher probability of observing an effect on morphology, hatching, malformations and mortality. In addition, we observed biochemical and behavioral damage caused in adult phase. Taken together, our data suggest damage to the embryonic, larval and adult development of zebrafish, which suggests harm to the health of fish and other aquatic organisms exposed to formulations containing glyphosate.